A Critical Look at Bilingual Physical Education in Spain - Martínez-Hita, Francisco José (Acta Paedagogica Vilnensia, 2025)
The main objective of the article has been to make a review of the most controversial aspects of bilingual education, mainly focusing on the subject of Physical Education. To this end, a search of the scientific literature was carried out in the main databases (Dialnet, Google Scholar, and SCOPUS) taking into account articles dealing with bilingual education, CLIL and Physical Education. In this way, a series of factors have been found that may go unnoticed and are not politically correct to publish as they are criticisms of the fashionable educational trend, bilingualism. The aspects dealt with are included in the following points: the content of the subject to be taught, motivation problems in students, difficulties and exhaustion on the part of teachers, the questioning of an inclusive school and analysis at a political level. These points are firstly discussed in general terms and, after that, more deeply in relation to the subject of Physical Education. All these aspects show that the Spanish educational system is at a crossroads in which it must reflect on the consequences of these changes and propose new alternatives.